Project learning, knowledge transfer and the adoption of innovation in project-based organizations - Zhou, Shijin (2017)
This doctoral thesis aims to explore the innovation adoption process in project-based organizations. In particular, I developed a theoretical framework that explains how intra- and inter- project learning influenced by different management practices. I further generated various hypotheses based on the conceptual framework by conducting qualitative interviews. Empirically, I used survey data to test those hypotheses. I collected data from 147-construction industry, most of the companies were contractors and real estate companies. The results strongly support our hypotheses and suggest that different management practices facilitate different types, i.e. tacit and explicit, knowledge transfer among projects and it further influences speed of innovation adoption and speed of innovation routinization. This dissertation contributes to management theory and practice by establishing a comprehensive framework which explains how different types of knowledge flows among different types of projects, i.e. innovative and routine projects, finally influence innovation adoption behavior of project-based organizations. Overall, this research has important implications for how project-based organizations can enhance innovation adoption and routinization to realize the economies of repetition.